Natural history of a cohort of ABCD1 variant female carriers. (9th November 2018) - Schirinzi, T.; Vasco, G.; Aiello, C.; Rizzo, C.; Sancesario, A.; Romano, A.; Favetta, M.; Petrarca, M.; Paone, L.; Castelli, E.; Bertini, E. S.; Cappa, M.
Abstract : Background and purpose: The therapeutic scenario of X‐linked adrenoleukodystrophy (X‐ALD) is rapidly changing. Whereas the disease is well characterized in men, the condition remains to be fully clarified in women carrying ATP binding cassette subfamily D member 1 ( ABCD1 ) variants. Specifically, data on clinical progression are needed, in order to recommend any appropriate management. The objective of this study was to outline the natural history of a cohort of untreated ABCD1 heterozygous female carriers. Methods: Longitudinal data from a single‐center population of 60 carriers were retrospectively reviewed. Demographics, anthropometrics, serum very long chain fatty acid (VLCFA) levels, clinical parameters and the Adult ALD Clinical Score (AACS) were collected from every recorded visit in a 7‐year period and analyzed to define the phenotype modifications, to determine factors associated with clinical features, and to estimate the annual progression rate and the subsequent sample size for interventional trials. Results: Thirty‐two patients were eligible for the study, and 59.4% were symptomatic at baseline. Clinical severity worsens with age which increases risk of symptom onset, the cut‐off of 41 years being crucial for phenoconversion. VLCFA levels were not predictive and did not change over time. Symptomatic carriers were followed up for 3.45 ± 2.1 years. The AACS increased at an annual rate of 0.24 points. The estimated sample size for 30% reduction in annual progression at 80% power was 272. Conclusions: This study provides data on the natural disease progression of untreated ABCD1 heterozygous female carriers, demonstrating the relevance of aging. The estimated annual increase of the AACS will be useful for future interventional studies.